New records of the invasive pest Drosophila suzukii (Matsumura) (Diptera: Drosophilidae) in the South American continent - Lavagnino, Nicolas Jose; Diaz, Beatriz Maria; Cichon, Liliana; De La Vega, Gerardo; Garrido, Silvina Alejandra; Lago, Jonatan; Fanara, Juan Jose (Sociedad Entomológica Argentina, 2018)
The present study reports new presences of Drosophila suzukii (Matsumura, 1931) (Diptera: Drosophilidae) in four localities in Argentina, extending its geographical range in South America. Among the new records, one is located in Mesopotamia region in eastern Argentina, where flies were captured around orange and mulberry orchards. The other record is located at Ticucho, Province of Tucumán, northwest from the previous record, where flies were collected from an unknown host, possibly Opuntia cactus. The other two captures of D. suzukii were performed in raspberries plantations located at the Patagonia region, and represent the southernmost record of this species in South America. All previous reports of D. suzukii in South America are also presented, as a review of the invasion of this pest species to the continent. The data support the scenario of an incipient invasion of D. suzukii in southern latitudes of South America. The geographical distribution of D. suzukii to new areas could imply damages and economic losses for regional economies